SPORTS CELEBRITIES AND THEIR IMPACT ON CONSUMER ATTITUDES (Heritage, 2023)
Sports celebrities are often considered heroes both locally and internationally. The behavior of these athletes on the field, where they excel as leaders of their teams, along with healthy values in their private lives, often enriched by philanthropic activities, do not escape the attention of sports marketing experts. With a sports personality whose image is consistent with the company's brand, a mutually beneficial partnership may be established. Athletes can earn substantial additional profits, while companies can enhance their brand image and gain a competitive advantage. Today, the digital environment has made this marketing strategy even more effective, since famous sports figures are better able to directly and effectively influence the attitudes of sports consumers (their fans). The problem arises, however, when sports celebrities damage their own reputation with inappropriate behavior. Sports celebrities can also damage the reputation of their sports clubs, as well as the reputation of the brands they endorse and/or promote. This situation is especially problematic for brands when negative electronic word-of-mouth communication (eWOM) causes incalculable damage to the company's reputation.
Keywords: Image of sports celebrities, Sports marketing, Digital environment, Sports consumers' attitudes, Brand